Revue de littérature du burnout dans le milieu sportif : vers une opérationnalisation des conceptualisations et une meilleure compréhension de ce phénomène - Isoard-Gautheur, S.; Guillet-Descas, E.; Ferrand, C. (Movement & Sport Sciences - Science & Motricité, 2017)
The goal of this article is to present an exhaustive and critic review of athlete burnout literature. Different studies have highlighted that the risk of burnout seems to be related to stress, a "feeling of being trapped", an exclusive athletic identity, a perception of control by significant others, non-satisfaction of basic psychological needs, low self-determined motivation, mastery and performance avoidance goals, and inappropriate forms of perfectionism. However, some limitations are emerging, particularly in measurements, the theoretical models being used and the studied population. Future research should be longitudinal and qualitative, encompass all of the presented models, and examine a more differentiated population.